Distinguishment of Sentence Patterns in Printed and Digital Publications - Ahsa, Zepina Julia Purnama; Afifah, Wiwiek (SENTRI: Jurnal Riset Ilmiah, 2026)
The development of information technology has transformed the way news is produced and consumed, affecting the sentence patterns and structures used in both print and digital media. This study aims to analyze the differences in sentence patterns between the two media types using a descriptive qualitative approach. Data were collected from 40 news articles taken from national print media and popular digital news portals. The analysis was conducted based on sentence length, sentence type, use of clauses, and style of information delivery. The results show that print media tend to use longer and more complex sentences with a higher average number of clauses, in line with Chomsky’s generative syntax framework. Digital media, on the other hand, frequently employ shorter and simpler sentences, consistent with Flesch’s readability principles. The differences in writing styles across both media support Leech’s view that linguistic style is influenced by communicative goals and the medium of delivery. In addition, the contrast in discourse structures aligns with van Dijk’s framework on news presentation strategies that emphasize clarity and accessibility. This study concludes that differences in sentence patterns between print and digital media represent a form of linguistic adaptation shaped by audience needs and the characteristics of each medium.